Analisis Reformasi Pendidikan dalam Mewujudkan Pemerataan Kualitas Pendidikan di Indonesia - Mgs Ahmad Wahyudi; Achmad Lutfi (Jurnal Administrasi Publik (Public Administration Journal), 2019)
Education is one of the main focuses of all countries in developing the quality of Human Resources as a national development tool. Educational reforms are improved according to the times and changes in social, economic and political conditions. The purpose of this paper is to find out the bright spots of the implementation of the new zoning system applicable in Indonesian education by looking at various comparisons of other countries that have already applied. Some other writers still have pros and cons with the zoning system starting from the implementation, benefits, and even other things that affect the quality of education in Indonesia, namely the needs of teaching staff. In order to find a problem approach, the authors use theoretical references from Viennet and Pont. Data collection was collected from various education policy books, journals related to the zoning system, publications from the Ministry of Education and the Central Statistics Agency and then drawn conclusions as a result of the journal that was analyzed qualitatively. Developed countries have implemented a zoning system for schools to overcome conducive classrooms, but there are new problems facing developed countries today with zoning conditions. The implications of the developed countries' zoning system can be used as material for the evaluation of the Indonesian government to avoid the same thing. This paper concludes that equitable distribution of facilities and infrastructures as well as the quality of teachers and the needs of the number of teachers are important keys in implementing the zoning system to run as expected.